Analisis Kesalahan Berbahasa Bidang Fonologi pada Wawancara Eksklusif Ganjar Pranowo dan Piala Dunia di Youtube Mata Najwa - Setiyani, Indah; Fatqia Rizki Amalia Utomo (Kajian Bahasa dan Sastra (KABASTRA), 2023)
The research is based on language errors in the field of phonology in exclusive interviews with Ganjar Pranowo and the World Cup in Mata Najwa. The research was conducted by applying a qualitative descriptive method. The purpose of this research is to show and describe language errors in the field of phonology involving speech sounds. The data in this study are in the form of primary data, namely narratives in exclusive interviews with Ganjar Pranowo and the World Cup in Mata Najwa and secondary data derived from written data from literature review. The data collection technique was carried out by observing and noting techniques. Data analysis was carried out with the stages of providing data, data reduction, data presentation, and drawing conclusions. Based on the results of the study, the data was categorized into 3 things namely, 12 phoneme omission data, 7 phoneme addition data and 16 phoneme change data.